Analisis Manajemen Risiko Dan Pengendalian Intern Pada Pengadaan Jasa Konstruksi (Studi Kasus Pengadaan Jasa Konstruksi Pada SKPD Di Lingkungan Pemerintah Provinsi Sumatera Barat) - elvita darma (Jurnal Pembangunan Nagari, 2017)
This study aims to identify and classify the risks of occur in the implementation of construction services procurement, an analyzed and assess the risks that arise in the procurement process of construction services and obtained the information about internal controls that have been done by the user. The sample of this research is 2 (two) SKPD in West Sumatera Province that is Office of Infrastructure of Road Spatial and Settlement and Water Resources of Management Office. By using FMEA method, the critical risk is obtained which is then analyzed further by using RPN. The study concluded that the presence of risks that occur during the process of procurement of construction services in the environment SKPD in West Sumatra Provincial Government. The main factors causing this risk are can be in some aspects such as intimidation from provider, LSM, law of enforcement officer and boss towards officers/committees of procurement / Pokja ULP. Then on the planning needs of KPA/ PPK and PPTK, the factors causing the risk are seen in some cases such as the procurement budget is not approved, the available budget is not sufficient and the TOR/KAK can not be used as a reference in the activity of implementation. Then, for the implementation stage there are in the late work, the lack of volume, the work can not be completed by the provider, the failure of the work due to natural disaster, and in the post of procurement/maintenance stages the procurement of construction services have not been utilized, Natural disaster occur, and not implemented FHO to work of constructions. Then when viewed the main risk of factors to the recipient of the work committee is the risk associated with the legal apparatus. Risk management and internal control over the procurement of construction services shall be conducted by all parties having an interest in risk control on the procurement of construction services within the SKPD of West Sumatra Province.